THE ROLE OF MOVING GAMES IN IMPROVING STUDENT ACTIVITY: THE ROLE OF MOVING GAMES IN IMPROVING STUDENT ACTIVITY - to'ychiyev, sobir (Физическое воспитание, спорт и здоровье, 2022)
The article emphasizes the important pedagogical significance of the use of national action games in the education system. Because national action games strengthen the health of students, develop such qualities as endurance, agility, speed, which in turn serve to instill in the citizen the qualities of social activism.